2021
DOI: 10.1177/14791641211058856
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of diabetic nephropathy in patient with type 2 diabetes mellitus: A review of the literature

Abstract: Type 2 diabetes mellitus is a pathology of heterogeneous etiology characterized by hyperglycemia resulting from lack of insulin action, insulin secretion, or both, and the population with diabetes mellitus is predicted to be about 439 million worldwide by 2030. Prolong diabetes has been related with microvascular complications especially diabetic nephropathy. DN is the most common complication of type 2 diabetes mellitus, and it is the leading cause of end-stage renal disease worldwide. It is crucial to diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 63 publications
0
51
0
6
Order By: Relevance
“…Ren et al [ 16 ] found that inflammatory factors such as interleukin (IL)-6, hypersensitive c-reactive-protein (hs-CRP), and tumor necrosis factor- α (TNF- α ) in patients with diabetic nephropathy accelerated the renal vascular sclerosis lesions in the body, which reduces the vascular elasticity and stimulates the proliferation of glomerular thylakoid cells in the body, thereby aggravating the disease. Thipsawat et al [ 17 ] stated that the control of inflammatory response and proteinuria in patients with diabetic nephropathy contributed to the alleviation of impaired renal function in patients. Vlachou et al [ 18 ] demonstrated that effective nursing interventions in patients with diabetic nephropathy treated with hemodialysis mitigated the inflammatory response and improved the patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al [ 16 ] found that inflammatory factors such as interleukin (IL)-6, hypersensitive c-reactive-protein (hs-CRP), and tumor necrosis factor- α (TNF- α ) in patients with diabetic nephropathy accelerated the renal vascular sclerosis lesions in the body, which reduces the vascular elasticity and stimulates the proliferation of glomerular thylakoid cells in the body, thereby aggravating the disease. Thipsawat et al [ 17 ] stated that the control of inflammatory response and proteinuria in patients with diabetic nephropathy contributed to the alleviation of impaired renal function in patients. Vlachou et al [ 18 ] demonstrated that effective nursing interventions in patients with diabetic nephropathy treated with hemodialysis mitigated the inflammatory response and improved the patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in pulmonary ventilation and diffusion function are associated with the development of DN [ 20 ]. DN poses a significant impairment of the pulmonary function indicators FEV1 and FVC, and this impairment is significantly associated with an increased rate of abnormal proteinuria (urinary protein/urinary creatinine ratio) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of biomarkers are proteins, lipids, microRNAs, genomic, etc. Plenty of biomarkers associated with DKD were found in recent years, such as serum cystatin C, neutrophil gelatinase-associated lipocalin (NGAL), N-acetyl-β-D-glucosaminidase (NAG), and serum homocysteine (Hcy) [12].…”
Section: Introductionmentioning
confidence: 99%